BNPB Performance in Disaster Management in Indonesia: Follow-up Recommendations - Mayasari, Shinta; Wulandari, Christine; Sukohar, Asep; Bakri, Samsul (Universitas Sang Bumi Ruwa Jurai, 2024)
Law Number 24 of 2007 concerning Disaster Management is the main legal basis for disaster management in Indonesia. BNPB as one of its products has the functions of prevention, preparedness, emergency response, as well as disaster rehabilitation and reconstruction. A qualitative narrative approach was used to analyze BNPB's performance and produce follow-up recommendations. Its effectiveness also still varies due to differences in potential and challenges in various regions in Indonesia. A number of follow-up recommendations are provided in this article to improve BNPB's performance in disaster management in Indonesia. BNPB's performance in recent years has been quite good and needs to be appreciated. BNPB has succeeded in reducing the trend in the number of fatalities due to disasters, but it needs to improve in SPD technology through the CSR program. BNPB has succeeded in establishing Destana, but needs to look for more fundings such as from village fund allocations and encourage disaster education as local content in school curriculum. BNPB's performance in its emergency response has not optimal, overlapping regulations between the central and regional governments needs to be clarified. Meanwhile, disaster rehabilitation and reconstruction performance is more focused on short-term infrastructure and economic recovery. BNPB can coordinate with health services provided by BPJS Health which provides psychological and mental health services for long-term recovery of the social and psychological aspects of disaster victims.